Numerical Analysis on Continuum Damage Mechanism of Thermoplastic Composite Pipe (TCP) - Mohd Nor Azami, Aina Syahira (IRC, 2020)
The purpose of this paper is to produce a material study on Thermoplastic Composite Pipe (TCP) which consists of PE80, Glass reinforced polymer and PE100 materials. The proposed model used stress-distribution analysis and thermal-stress distribution analysis for onshore pipeline environment under internal pressure load by using Finite Element Analysis in Abaqus CAE software. The composite model has been tested under internal pressure value of 1.72 MPa and 42 MPa and variation temperature dependent data. The stress-strain diagram of the TCP composite has been obtained to characterize the mechanical properties of the composite under internal pressure load.